Prediction Potential Chlorogenic Acid As Inhibitor Ace (In Silico Study) - Yohanes Bare; Dewi Ratih Tirto Sari; Yoga Tribakti Rachmad; Sri Sulistyaningsih Natalia Daeng Tiring; Apriani Herni Rophi; Fitra Arya Dwi Nugraha (UNIVERSITAS NEGERI PADANG, 2019)
One of the derivatives of flavonoid explored is chlorogenic acid. Chlorogenic acid has antioxidant and anti-inflammatory activity. Hypertension has support for Angiotensin converting enzyme (ACE) which has a role in regulating the renin-angiotensin system. Hypertension therapy is carried out in inhibit ACE pathway. This study aims to analyze and assess the potential of chlorogenic acid as an anti-hypertensive material by inhibiting the work of ACE. The method used is in silico. Chlorogenic acid ligand was obtained from PubChem while ACE was obtained from RCSB. Interaction of ligand and protein using HEX 8.0.0. Analysis and visualization of the results of interactions using Discovery Study Version 4.1. The results showed an interaction between ligand and protein, namely interactions that occur between chlorogenic acid and sixteen amino acid residues. This interaction produces energy of -292.5cal / mol. This interaction approved the ACE block in the AT-I transformation towards AT-II. Chlorogenic acid has potential as an anti-hypertension material.